In-Silico Screening of Mitragynine Derivates from the Genus Mitragyna Korth Targeting the Main Protease of the SARS-COV-2 - Islamudin Ahmad; Nur Masyithah Zamruddin; M. Arifuddin; Yuspian Nur; Firzan Nainu (Journal of Tropical Pharmacy and Chemistry, 2023)
Coronavirus Diseases 2019, caused by SARS-CoV-2, has been a significant threat to global public health. Unfortunately, effective COVID-19 vaccines and clinically-proven anti-SARS-CoV-2 drugs remain unavailable. This study was carried out aiming to predict the potential effect of mitragynine derivates from the Genus Mitragyna Korth as an inhibitor of Mpro, the main protease of the SARS-CoV-2, by in silico molecular docking study. The crystal structure of the main protease of SARS-CoV-2 as an active site target was obtained from the PDB database (rcsb.org) with PDB ID: 5R84 and 6LU7 with the native ligand of Z31792168 and N3, respectively. The analysis of in silico molecular docking was conducted using Autodock 4.2.6 (100 docking runs). The central grid was placed on HIS41 and CYS145 with a grid box comprised of 40x30x34 (for protein 5R84) and 36x62x40 (for protein 6LU7) points spaced by 0.375 Å was centered on the active site of X=9,812; Y=-0,257; Z=20,849 and X=-9.732; Y=11.403; X=68,483 (XYZ-coordinates), respectively. Our research indicated that mitrjavine and ajmalicine exhibit greater potential inhibition of the active site on the Mpro of SARS-CoV-2, even stronger than native ligands. We believed that these compounds are promising candidates to be examined in further COVID-19 drug discovery studies.